2014
DOI: 10.2147/ijn.s53538
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba: a natural reducing agent for the synthesis of cytocompatible graphene

Abstract: Background Graphene is a novel two-dimensional planar nanocomposite material consisting of rings of carbon atoms with a hexagonal lattice structure. Graphene exhibits unique physical, chemical, mechanical, electrical, elasticity, and cytocompatible properties that lead to many potential biomedical applications. Nevertheless, the water-insoluble property of graphene restricts its application in various aspects of biomedical fields. Therefore, the objective of this work was to find a novel biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 79 publications
8
54
0
2
Order By: Relevance
“…28 GO induced cytotoxicity in human neuroblastoma SH-SY5Y cells at higher concentrations of 80 µg/mL at 96 h in a dose-and timedependent manner, 29 and GO nanoribbons induced toxicity by generation of reactive oxygen species (ROS), impairment of mitochondrial membrane potential (MMP), and formation of autophagosomes (APs), 30 which also depends on the size, charge, surface chemistry, and physical and chemical nature of the synthesized graphene. 27,28,31,32 On the other hand, the biocompatibility was analyzed using a variety of chemically and biologically functionalized graphene in several cell lines. For example, GO composites containing Tween-20 and chemically reduced GO showed excellent stability in water and were non-toxic to three different mammalian cell lines, including Vero cells, embryonic bovine cells, and CrandellRees feline kidney cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 GO induced cytotoxicity in human neuroblastoma SH-SY5Y cells at higher concentrations of 80 µg/mL at 96 h in a dose-and timedependent manner, 29 and GO nanoribbons induced toxicity by generation of reactive oxygen species (ROS), impairment of mitochondrial membrane potential (MMP), and formation of autophagosomes (APs), 30 which also depends on the size, charge, surface chemistry, and physical and chemical nature of the synthesized graphene. 27,28,31,32 On the other hand, the biocompatibility was analyzed using a variety of chemically and biologically functionalized graphene in several cell lines. For example, GO composites containing Tween-20 and chemically reduced GO showed excellent stability in water and were non-toxic to three different mammalian cell lines, including Vero cells, embryonic bovine cells, and CrandellRees feline kidney cells.…”
Section: Introductionmentioning
confidence: 99%
“…34 Lee et al 35 demonstrated that graphene-and GO-coated substrates accelerated mesenchymal stem cell (MSC) adhesion, proliferation, and differentiation. Biologically functionalized graphene showed excellent biocompatibility in various cell lines, such as mouse embryonic fibroblast cells, 26 human breast cancer cells, 31 and human embryonic kidney (HEK) 293 cells. 36 Although both AgNPs and graphene are widely known for their outstanding antimicrobial and anticancer activity in a variety of bacteria and cell lines, respectively, the disadvantage of AgNPs is their strong tendency to aggregate in aqueous solutions and susceptibility to aggregation into large particles owing to their high surface energy, resulting in deterioration of their unique chemical properties and loss …”
Section: Introductionmentioning
confidence: 99%
“…The number of publications is very large and most of the studies refer to the biosynthesis of metal NPs, but also found results about the biosynthesis of nanomaterials such as graphene (Gurunathan et al, 2014). It has a series de NPs de metales, aunque también se encuentran resultados acerca de la biosíntesis de nanomateriales como el grafeno (Gurunathan et al, 2014).…”
Section: Nanoparticles Biomanufacturingmentioning
confidence: 99%
“…The number of publications is very large and most of the studies refer to the biosynthesis of metal NPs, but also found results about the biosynthesis of nanomaterials such as graphene (Gurunathan et al, 2014). It has a series de NPs de metales, aunque también se encuentran resultados acerca de la biosíntesis de nanomateriales como el grafeno (Gurunathan et al, 2014). Se dispone de una serie de revisiones de literatura que señalan muchos casos específicos, incluyendo las especies vegetales utilizadas para la biofabricación de NPs, así como los elementos transformados a NPs (Iravani, 2011;Baker et al, 2013;Rai y Yadav, 2013;Pardha-Saradhi et al, 2014b;Ahmed and Ikram, 2015;Keat et al, 2015).…”
Section: Nanoparticles Biomanufacturingunclassified
“…GO reduction was also caused by the pollen extract of the exotic ornamental tree Peltophorum pterocarpum. (Rahman et al, 2014) By reduction of Ginkgo biloba (Gurunathan et al, 2014) rGO which had no toxic properties was prepared, while it was biocompatible with human tumour cells.…”
Section: Plant Effect On Substances Made Of Graphenementioning
confidence: 99%